The Risk of Cancer in Patients With Obsessive-Compulsive Disorder: A Nationwide Population-Based Retrospective Cohort Study. Issue 9 (March 2016) - Shen, Cheng-Che; Hu, Li-Yu; Hu, Yu-Wen; Chang, Wen-Han; Tang, Pei-Ling; Chen, Pan-Ming; Chen, Tzeng-Ji; Su, Tung-Ping
Abstract : Abstract: Previous studies suggest a link between anxiety disorders and cancer. The aim of the study was to evaluate the risk of cancer among patients with obsessive-compulsive disorder (OCD) using a nationwide population-based dataset. We recruited newly diagnosed OCD patients without antecedent cancer from the Taiwan National Health Insurance Research Database between 2002 and 2011. The standardized incidence ratios (SIRs) were estimated for 22 specific cancer types among OCD patients and we determined the SIRs for subgroups according to age and sex group. In addition, because of a potential detection bias, a subgroup analysis stratified with the duration of the OCD diagnosis was carried out. Among the 52, 656 OCD patients, who were followed up for 259, 945 person-years (median follow-up = 4.9 years), there were 718 cases of cancer. Patients with OCD did not exhibit an increased overall cancer risk relative to the general population (SIR 1.05, 95% confidence interval [CI] 0.98–1.13). An increased SIR was observed among OCD patients only within the first year of OCD diagnosis (SIR 1.21, 95% CI 1.01–1.43). This study indicated that the overall cancer risk was not elevated among OCD patients. An increased SIR observed among OCD patients within the first year of OCD diagnosis may be caused by a surveillance bias, and because paraneoplastic manifestations presented with obsessive-compulsive behaviors. Prospective study is necessary to confirm these findings.